Essential neuromuscular advice for pathologists: Limb Girdle Muscular Dystrophy (second of two parts) - Ana Cotta; Elmano Carvalho; Antonio Lopes da-Cunha-Júnior; Julio Salgado Antunes; Francineide Sadala de Souza; Heveline Becker de Moura; Andreia Portilho de Brito Pinto; Jaquelin Valicek; Monica Machado Navarro; Frederico Godinho; Eni Braga da Silveira; Maria Isabel Lima; et al. (Surgical and Experimental Pathology)
Abstract Background Limb Girdle Muscular Dystrophy is defined as a group of progressive autosomal recessive (85%, 28 genes) and autosomal dominant (15%, 5 genes) muscular dystrophies described in at least two unrelated families, affecting individuals that achieve independent walking, with predominant proximal muscles weakness at presentation, elevated serum creatine kinase activity, dystrophic changes on muscle biopsy, and degeneration on muscle imaging over the course of the disease. Main body The aims of this review are: (1) to show the recent Limb Girdle Muscular Dystrophy (LGMD) genetic classification illustrated with clinical and physiopathological characteristics, and cellular localization of the main gene products; (2) to present muscle radiophenotypes with an algorithm for differential diagnosis; (3) to show the role of muscle biopsy for phenotypic characterization, and pathogenicity confirmation in the era of surgical-molecular pathology. Conclusion Pathologists may be aware of clinical, neurophysiological, laboratorial, imaging, molecular, and muscle biopsy modalities to provide a precise phenotypic-genotypic diagnosis for adequate rehabilitation care, and genetic counselling.